2015
DOI: 10.1242/jeb.125799
|View full text |Cite
|
Sign up to set email alerts
|

Comparative limb bone loading in the humerus and femur of the tiger salamander Ambystoma tigrinum: testing the ‘mixed-chain’ hypothesis for skeletal safety factors

Abstract: Locomotion imposes some of the highest loads upon the skeleton, and diverse bone designs have evolved to withstand these demands. Excessive loads can fatally injure organisms; however, bones have a margin of extra protection, called a 'safety factor' (SF), to accommodate loads that are higher than normal. The extent to which SFs might vary amongst an animal's limb bones is unclear. If the limbs are likened to a chain composed of bones as 'links', then similar SFs might be expected for all limb bones because fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Differences in functional change between the forelimbs and hindlimbs have been noted for other taxa spanning evolutionary transitions in habitat [11]. The reduction of propulsive force from the hindlimbs that appears likely with the loss of ankle flexion in tortoises may contribute to their inability to swim into flowing water during our trials.…”
Section: Discussionmentioning
confidence: 67%
“…Differences in functional change between the forelimbs and hindlimbs have been noted for other taxa spanning evolutionary transitions in habitat [11]. The reduction of propulsive force from the hindlimbs that appears likely with the loss of ankle flexion in tortoises may contribute to their inability to swim into flowing water during our trials.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, the shape of the salamander forelimb may reflect its loading regime and be stiffer in these directions. Bone loading analyses and second moment of area calculations on the humeri of the terrestrial A. tigrinum confirmed that resistance to bending was greatest in the dorsocaudal direction, reflecting the directionality of the ground reaction forces ( Kawano et al. 2016 ).…”
Section: Use Casesmentioning
confidence: 84%
“…To elicit self-righting attempts, turtles were inverted and placed on their carapace, such that the dorsal surface of the head contacted a custom-built force platform (K&N Scientific, Guilford, VT, USA). Specifications of the force platform and signal processing are reported by Butcher and Blob (2008) and Kawano et al (2016). Three-dimensional forces were recorded at 5000 Hz using a customwritten LabVIEW (v.6.1, National Instruments, Austin, TX, USA) routine, while being filmed with digitally synchronized high-speed video in dorsal and frontal views at 100 Hz (Phantom v 5.1, Vision Research Inc., Wayne, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%